158k views
0 votes
If f(x)= 2x +4 and g(x)= 3x - 7; then find g(g(3)).

PLEASE HELP

1 Answer

7 votes

Final answer:

To find g(g(3)), substitute 3 into the function g(x) and then substitute the result into the function again. The final result is -1.

Step-by-step explanation:

To find g(g(3)), we need to substitute 3 into the function g(x) and then substitute the result into the function again. Let's go step by step:

  1. First, substitute 3 into g(x): g(3) = 3(3) - 7 = 9 - 7 = 2
  2. Next, substitute the result (2) into g(x) again: g(2) = 3(2) - 7 = 6 - 7 = -1

Therefore, the final result is -1.

User Mackworth
by
5.8k points